PENGARUH FAKTOR-FAKTOR FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Devara Amanda Chairunisya, (2022)
This study is the result of a quantitative test with the aim of showing and assessing the effect of pentagon fraud with variables namely financial target, ineffective monitoring, change in auditor, change in director, and frequent number of CEO pictures on financial statement fraud. The method of measurement uses secondary data, and the determination of the sample is carried out by the purposive sampling method. The sample of this research is 37 property and real estate sector companies listed on the Indonesia Stock Exchange in 2018 - 2020. The statistical method used in this study is logistic regression analysis. The results of this study indicate that the ineffective monitoring variable has a significant effect on fraud in financial reporting. However, financial targets, change in auditors, change in directors, and frequent number of CEO pictures have no effect on fraudulent financial statements. Simultaneously or simultaneously the dependent variables have a significant influence on financial statement fraud.